Willingness to communicate from an English as an International Language (EIL) perspective: The case of Macau. (December 2019) - Cao, Yiqian Katherine; Wei, Wei
Abstract: The study was conducted in Macau, a sociolinguistically diverse context with sixty-two first-year and second-year university students. Semi-structured interview was used as an instrument for data collection for this exploratory study. The students were asked questions regarding their willingness to communicate (WTC) using different varieties of English in face-to-face communication and communication in the social media contexts. The results indicate that the participants are aware of the status of English as an international language and can identify the different English varieties in Kachru's (1986) concentric circles. The participants have reported a high willingness to communicate in two standard English varieties; that is, American English and British English for face-to-face communication and social media contexts. The study has also revealed an emergence of the Chinese variety of English in that the participants hold a positive attitude towards Chinese English and are willing to use it in monolingual classrooms and in the case of out-of-class events in which the speakers share the first language and culture that Chinese English is used.